The interests of white‐collar workers and their representation in the German manufacturing sector: new initiatives, opportunity structures, framing and resources. Issue 4 (17th June 2016) - Haipeter, Thomas
Abstract: In the German manufacturing sector, white‐collar workers have outpaced blue‐collar workers in numbers. Therefore, unions and works councils have launched initiatives to attract, mobilise and organise white‐collar workers. The analysis is drawing on a conceptual framework that looks at the opportunity structures, framing processes and resources of the initiatives.